The 22-day revolution cookbook : unleash the life-changing health benefits of a plant-based diet - Borges, Marco (Celebra, 2016)
"From the author of the massive bestseller The 22-Day Revolution comes a plant-based cookbook full of the tools you need to live a healthier, happier life, with more than 150 all-new, mouth-watering recipes and customizable meal plans to create your own 22-Day Revolution program. Since health expert and exercise physiologist Marco Borges first introduced his groundbreaking plant-based program in The 22-Day Revolution, the revolution has become a movement, motivating thousands of readers and followers worldwide how to take control of their health, lose weight, and create better habits in just 22 days. Now, Marco shares more than 150 mouthwatering recipes he's cultivated over the years working with his high-profile clients including Jay-Z, Jennifer Lopez, Pharrell Williams, Gloria Estefan, Shakira, and Beyonce--the recipes that have created some of the hottest bodies in Hollywood and helped his clients combat serious health concerns like high cholesterol, heart disease, high blood pressure, and diabetes. If you're looking to kick-start a healthy lifestyle, Marco has created four customizable meal plans that will help you reach your weight loss and fitness goals--from serious weight loss, to maintaining, to building muscle. From the decadent classics Mac 'n' Cheese and a juicy Black Bean Burger to the innovative flavors of the Teriyaki Veggie Bowl with Meatless Balls and Walnut Chili--The 22-Day Revolution Cookbook will delight your family and bring the incredible benefits of a plant-based lifestyle into your home. Foreword by Ryan Seacrest"--